Heartbreak Bay - Caine, Rachel (Caine, Rachel. Stillhouse Lake series, 2021)
"A car submerged in a remote pond. The bodies of two girls strapped into their seats. The mystery of their mother, vanished without a trace, leads Gwen Proctor and Kezia Claremont into dangerous territory.On the surface, Gwen's life is good - two children approaching adulthood, a committed partner, and a harrowing past dead and gone. But that past is attracting the attention of someone invisible- and unstoppable. Trouble's just beginning. So is the body count in this backwoods Tennessee town. As threats mount and Gwen's hunted by an enemy who pulls all the strings, Kezia has her back. But working to solve these vicious and unreasonable crimes will expose them both to a killer they can't for the life of them see coming."--Publisher.